Factors Affecting Cases of Dengue Hemorrhagic Fever in Riau Province - fitriani, selvi; sirait, haposan; nurnisaa (International Journal of Mathematics, Statistics, and Computing, 2024)
One infectious disease that has a high morbidity and mortality rate is Dengue Hemorrhagic Fever. Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus transmitted through the bite of the Aedes aegypti mosquito. In general, the habitat of Aedes mosquitoes is in areas with tropical climates, high rainfall, and hot and humid temperatures. The number of patients and the area of distribution are increasing along with increasing mobility and population density. Improper sanitation can also be a cause of DHF. In Riau province, dengue cases in 2022 continue to increase compared to 2021, with the most cases in Pekanbaru City. This study was conducted to see the factors that influence dengue cases in Riau Province. Using multiple linear regression can measure what factors affect the number of dengue cases. From the results, it was found that population density and sanitation had a significant effect on dengue cases in Riau Province. And judging from the coefficient of determination, it can be interpreted that the variables of population density (X1) and sanitation (X2) simultaneously affect the variable of dengue cases (Y) by 77.8%. While the remaining 22.2% was influenced by other variables that were not studied in this study